Development and Validation of Android-Based Mobile App for Self-Controlling Excess Body Fluids in Chronic Renal Failure Patients Undergoing Hemodialysis: Original Article - Faridah, Virgianti Nur; Hidayati, Nur; Rokhman, Abdul; Saputra, Bagus Dwi; Bachri, Saiful (Babali Publisher, 2024)
Background: Chronic renal failure patients undergoing hemodialysis commonly experience excess fluid volume in the body. It is necessary to provide media which can be independently employed by the patients to control body fluids and prevent fluid overload. The purpose of the study is to develop an android-based application